PENYELESAIAN SENGKETA BATAS TANAH ULAYAT ANTARA NAGARI CANDUANG KOTO LAWEH KECAMATAN CANDUANG DENGAN NAGARI KOTO TINGGI KECAMATAN BASO KABUPATEN AGAM - Risa Irfaneni; Hayatul Ismi; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The problem of land disputes that often occur is due to the absence ofclear land boundaries and the non-fulfillment of the rights of indigenous peoples.The purpose of this thesis writer: First, to find out the causes of the communalland boundary dispute between Nagari Canduang Koto Laweh, CanduangDistrict, and Nagari Koto Tinggi, Baso District, Agam Regency. Second, to findout the settlement of communal land boundary disputes between NagariCanduang Koto Laweh, Canduang District, and Nagari Koto Tinggi, BasoDistrict, Agam Regency.This research is classified as a sociological research type, because theauthor directly conducts research on the locations or points examined to providea complete and clear picture of the problems examined. This research wasconducted in Nagari Canduang Koto Laweh, Canduang District and Nagari KotoTinggi, Baso District, Agam Regency, while the sample population was all partiesrelated to the problems studied in this study, data sources used, primary data andsecondary data, data collection techniques in this study by interviewing literaturereview and data analysis.From the research, there are two things that can be concluded. First, thefactors causing the dispute over customary land boundaries between NagariCanduang Koto Laweh and Nagari Koto Tinggi are unclear land boundariesbetween nagari. Disputes over customary land boundaries also occur due to non-fulfillment of the rights of indigenous peoples. Second, efforts to resolve landboundary disputes between Nagari Canduang Koto Laweh and Nagari KotoTinggi are customary, namely through deliberations, discussing about 7 times thepoint of boundary of Nagari land, but there is no result. Settlement of landboundary disputes is handed over to a third party, namely the Agam RegionalGovernment The author's suggestion, to both parties, namely Nagari Koto Tinggiand Nagari Canduang Koto Laweh, should better understand the benchmarkboundaries that have existed from the time of their ancestors to safeguard therights of indigenous peoples within them and to the Pemda Agam as a third partythat mediates disputes over the nagari boundaries in order to provide legalcertainty and protect the rights of indigenous peoples.Keywords: Land Boundary Dispute – ADR